Prostate Cancer Presenting with Parietal Bone Metastasis - Brahima Kirakoya; Abdoul Karim Pare; Babagana Mustapha Abubakar; Moussa Kabore (Case Reports in Urology)
Bone metastases from prostate cancer are very common. They are usually located on the axial skeleton. However, cranial bone metastases especially to the parietal bone are rare. We report a case of metastatic prostate cancer presenting with left parietal bone metastasis in a patient with no urological symptoms or signs. We should consider prostate cancer in any man above 60 years presenting unusual bone lesions.